A Case of Mistaken Identity: Antiphospholipid Syndrome with Predominant Neuropsychiatric Features - Grace E Jackson; Sedona AZ (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Despite the known association between autoimmune and psychiatric conditions, pertinent evaluations are often overlooked in clinical practice. The author of this report describes the successful identification and treatment of a patient whose myriad neuropsychiatric symptoms were ultimately attributable to antiphospholipid syndrome. The importance of comprehensive and persistent workups is emphasized, particularly in the context of individuals with pre-existing inflammatory diseases and/or cerebrovascular anomalies.